Dentigerous Cyst or Adenomatoid Odontogenic Tumor: Clinical Radiological and Histopathological Dilemma - Shivesh Acharya; Ashima Goyal; Vidya Rattan; Kim Vaiphei; Sarabjot Kaur Bhatia (Case Reports in Medicine)
Adenomatoid odontogenic tumor (AOT) is a well-recognised slow growing benign tumor derived from complex system of dental lamina or its remnants. This lesion is categorised into three variants of which the more common variant is follicular type which is often mistaken for dentigerous cyst. We present a case of AOT in a 14-year-old male who was misdiagnosed as dentigerous cyst. Clinical radiological and therapeutic characteristics of the case are commented on in detail.